The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12307-017-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition (EMT) in Metastatic Breast Cancer in Omani Women

Abstract: Breast cancer (BC) in Oman affects younger women and has a more aggressive course. Clinical and biological variables like age, pregnancy, tumor size, type, grade, receptor expression and proliferation predict disease aggression but there is no direct predictor of metastasis except lymphovascular invasion. Epithelial-mesenchymal transition (EMT) is characterized by epithelial cells losing epithelial and acquiring mesenchymal morpho-immunophenotypic characteristics. In tumors, EMT-like transitions may signify a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…The study done by Lakhtakia et al . showed that there is a strong correlation between LVI and vimentin expression 23. In the present study, in TNBC cases, the association between vimentin expression and the status of LVI and higher tumor grade was statistically significant.…”
Section: Discussionsupporting
confidence: 56%
“…The study done by Lakhtakia et al . showed that there is a strong correlation between LVI and vimentin expression 23. In the present study, in TNBC cases, the association between vimentin expression and the status of LVI and higher tumor grade was statistically significant.…”
Section: Discussionsupporting
confidence: 56%
“…28 The expression of Vimentin not only marks the EMT on tumour cells, but also lead to changes in morphology, motor ability, and adhesion ability: all of these are favourable for metastasis. 28 The expression of Vimentin not only marks the EMT on tumour cells, but also lead to changes in morphology, motor ability, and adhesion ability: all of these are favourable for metastasis.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…Some biomarkers have been used to prove EMT, including membrane proteins like E-cadherin show reduced expression or are converted to N-cadherin. 28 The expression of Vimentin not only marks the EMT on tumour cells, but also lead to changes in morphology, motor ability, and adhesion ability: all of these are favourable for metastasis. 29 And the Snail family can reduce the expression of E-cadherin, cytokeratins, and increase the expression of mesenchyme.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…In epithelial tumors such as breast tumor, the epithelial-mesenchymal transition (EMT) phenomenon can appropriately explain the processes of distant metastasis (10). Recent studies from gene profiling have revealed some genes that can be overexpressed within the EMT process causing its activation and leading to tumor progression and metastasis (11, 12). Moreover, the expression of these genes in the EMT process may be associated with other tumor-related behaviors including vascular and lymphatic invasions which play a critical role in planning distant metastasis (13).…”
Section: Introductionmentioning
confidence: 99%